Loneliness experience during distance learning among college students with ADHD: the mediating role of perceived support and hope. Issue 2 (4th March 2022) - Laslo-Roth, Roni; Bareket-Bojmel, Liad; Margalit, Malka
ABSTRACT: This study examined the predictive role of attention deficit disorders (ADHD) on the experience of loneliness among college students during the move to distance learning and social distancing policy during the COVID-19 pandemic. The study examined a serial multiple mediation of students' experiences with distance learning, perceived social support, and hope. We hypothesised that students with ADHD would experience social distress in addition to struggling with distance learning. However, we expect that social support and hope may mediate their loneliness. The sample consisted of 648 students (Mean age 27.99, SD – 7.08), in a medium size college in the centre of Israel. Participants were divided into two groups: 529 typical students and 119 students with ADHD. Loneliness, negative experiences during the use of distance learning, perceptions of social support, and hope were examined. Students with ADHD reported higher levels of loneliness and more negative experiences with distance learning than their peers. Results demonstrated that ADHD and negative experiences with distance learning predicted higher levels of loneliness, while college support and peer support in addition to hopeful thinking mediated these relations. The discussion focuses on the theoretical and practical aspects of loneliness and support while emphasising the therapeutic implications of hope.